DIGITAL TRANSFORMATION AND TEACHER'S SHIFTING ROLE THE IMPACT ON THE LEARNING ATTITUDE OF STUDENTS (CASE STUDY IN HIGH SCHOOL - Bahar, Yolanda; Ahmad, Riska; Nurfarhanah, Nurfarhanah; Ardi, Zadrian (RADJA PUBLIKA, 2022)
Students with positive learning attitudes have an effect on better learning outcomes than students with negative learning attitudes. The formation of negative learning attitudes in students due to digital transformation and shifts in the role of teachers, causing moral and personality degradation of students, lazy to learn and do assignments, passive or inactive in learning, unable to use technology wisely and there is an imbalance or disconnection of the process. learn how to teach. The purpose of this study was to analyze the learning attitudes of students due to digital transformation and shifts in the role of teachers, by focusing on three main components of attitudes, namely cognitive, affective and conative.The method used in this study is a qualitative method with a case study research model that examines students' learning attitudes. The data collection technique used is by observing students, interviewing three students, homeroom teacher, BK teacher and school principal, as well as analyzing documents obtained from schools. The data were analyzed through three stages, namely data reduction, data presentation and conclusions or verification.The results of this study indicate that digital transformation and shifting the role of teachers have an impact on students' learning attitudes, namely the formation of positive learning attitudes and negative learning attitudes. Positive learning attitudes are formed from understanding, feelings and tendencies to behave positively towards digital transformation and shifts in the teacher's role, while negative learning attitudes are formed from understanding, feelings and tendencies to behave negatively towards digital transformation and shifting teacher roles. So, it can be concluded that the learning attitude of students is a collection of cognitions that connect with knowledge, affection that connects with feelings or emotions so that it gives rise to a tendency, and connotations that show a behavior or learning habits of students.